Non-equipotential effect observed on the surface of Ti/Si under uniform illumination - Chunlian Mei; Shuai Liu; Anhua Dong; Xu Huang; Chongqi Yu; Hui Wang (New Journal of Physics, 2020)
In this letter, a non-equipotential surface photovoltaic effect is reported in nano metal–semiconductor structures. When the surface of the Ti/Si is uniformly illuminated by a beam of light, a controllable surface photovoltaic effect is observed on the metal side. The center of the surface presents a remarkably higher metallic potential than the surrounding region. The surface photovoltage is detected to be as high as 53 mV. Besides, it depends sensitively on the thickness and size of the metal films, demonstrating it is a unique feature of nano metal films. We ascribe this phenomenon to the boundary effect of photon-generated carriers in the ultrathin metal thickness. The theoretical calculations based on equivalent electron diffusion model are in great agreement with the experimental results. The results may promise some novel applications based on the nanoscale metal–semiconductor systems.